Penyuluhan Lieterasi Keuangan Bagi UMKM di Lingkungan RT 06 Curug Pondok Kelapa Duren Sawit - Wedia Hastuti; Irma Maria Dulame; Iman Sjamsu Rahardjo; Rida Justin Jacobalis; Ida Adhani (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute the economic backbone of the RT 06 community in Curug, Duren Sawit. However, preliminary observations indicated that 80% of business owners commingled personal and business finances, lacking formal cash flow records. This deficiency in financial literacy serves as a primary constraint on business sustainability. This community service initiative aimed to enhance financial management capacity through a Participatory Action Research (PAR) approach, utilizing an intensive mentoring framework. Fifteen MSME participants received targeted education on segregating bank accounts, training in simplified bookkeeping, and personalized coaching clinics over a four-week period. The results demonstrate a significant improvement in financial management capabilities, with 86.7% of participants successfully segregating personal and business finances. Furthermore, a 45% increase in participants' scores was observed between the pre-test and post-test assessments. Consequently, all participants have now adopted simplified bookkeeping systems, utilizing either conventional or digital methods. The findings suggest that a personalized mentoring strategy is more effective than traditional classroom-based instruction, as it addresses specific technical challenges and facilitates direct behavioral change. This program provides a scalable model for enhancing the financial resilience of MSMEs in similar contexts, enabling them to operate with greater efficiency, transparency, and improved capacity for long-term growth projections.